Analisis Hubungan Keadilan Organisasional dan Budaya Organisasional terhadap Komitmen Organisasional Karyawan Swalayan - Hery Verianto The (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The primary objective of this research is to examine and evaluate the impact of organisational justice and organisational culture on employee organisational commitment within the context of Garuda Mitra Supermarket Pontianak. The sample size for this study consisted of 69 individuals who were employed throughout the period in which this research was carried out. The employed study methodology entails a descriptive quantitative causal survey. The census sampling approach was employed, wherein all populations were utilised as samples. The data that was gathered was subjected to analysis using SPSS version 23. The hypothesis is tested using the statistical technique of multiple linear regression analysis. The findings of the study indicate that there is a positive and statistically significant relationship between organisational justice and employee organisational commitment. Additionally, the results demonstrate that organisational culture also has a positive and significant impact on employee organisational commitment. Furthermore, the study reveals that both organisational justice and organisational culture have a positive and significant influence on overall organisational commitment.